2016
DOI: 10.3998/ark.5550190.p009.519
|View full text |Cite
|
Sign up to set email alerts
|

Methods for synthesis of N-heterocyclyl/heteroaryl- α-aminophosphonates and α-(azaheterocyclyl)phosphonates

Abstract: This review describes the most frequently reported synthetic methods for N-heterocyclyl-α-aminophosphonic acids and their mono-or di-esters bearing a heterocyclic or heteroaryl system at the nitrogen atom, as well as methods for the synthesis of α-(azaheterocyclyl)phosphonates. The Pudovik and Kabachnik-Fields reactions are the main pathways for construction of these features besides other miscellaneous methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…[1][2][3][4] The synthesis of a-aryl-a-aminophosphonates can be carried out in two main routes: by the Kabachnik-Fields condensation, [5][6][7][8][9] or by the Pudovik (aza-Pudovik) reaction. [10][11][12][13] Although, the Pudovik addition, where a >P(O)H reagent, such as a dialkyl phosphite is added to the C ¼ N double-bond of imines, is simpler and widely applied, the Kabachnik-Fields condensation, in which an amine, an aldehyde or ketone and a >P(O)H species react in a one-pot manner, is also of an increased interest. Both reaction types were performed in the presence of a catalyst and/or a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The synthesis of a-aryl-a-aminophosphonates can be carried out in two main routes: by the Kabachnik-Fields condensation, [5][6][7][8][9] or by the Pudovik (aza-Pudovik) reaction. [10][11][12][13] Although, the Pudovik addition, where a >P(O)H reagent, such as a dialkyl phosphite is added to the C ¼ N double-bond of imines, is simpler and widely applied, the Kabachnik-Fields condensation, in which an amine, an aldehyde or ketone and a >P(O)H species react in a one-pot manner, is also of an increased interest. Both reaction types were performed in the presence of a catalyst and/or a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Abdel-Rahman et al [22,24,37] reported the synthesis of various isolated and/ or fused 1,2,4-triazine as anti-HIV and anticancer agents, where the most obtained systems exhibited very good to moderate activities. Based on these results, the newly synthesized compounds were evaluated against MCF 7 cell line cytotoxicity and antitumor cell according to the reported method [38].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…It is interesting to note that substituted pyrazoles exhibited a wide range of biological, pharmacological, and medicinal activities [15][16][17][18][19][20]. Recently, functionally 1,2,4-triazine derivatives showed an important biological activity such as anti-HIV, and anticancer [21], antioxidant [22], anti-inflammatory [23], antifungal [24], herbicidal [25] and antibacterial [26,27] agents. Also, 1,3,4thiadiazoles containingsmall heterocyclic nitrogen nucleus exhibited a greatspectrum biological activity as anti-inflammatory [28], anticancer [29,30], antimicrobial [31,32], anti-HIV, and antitumor [33], and antimycotic [34] agents.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that substituted pyrazoles exhibited a wide range of biological, pharmacological, and medicinal activities [15][16][17][18][19][20]. Recently, functionally 1,2,4-triazine derivatives showed an important biological activity such as anti-HIV, and anticancer [21], antioxidant [22], anti-inflammatory [23], antifungal [24], herbicidal [25] and antibacterial [26,27] agents. Also, 1,3,4thiadiazoles containingsmall heterocyclic nitrogen nucleus exhibited a greatspectrum biological activity as anti-inflammatory [28], anticancer [29,30], antimicrobial [31,32], anti-HIV, and antitumor [33], and antimycotic [34] agents.…”
Section: Introductionmentioning
confidence: 99%